Isonatraemic haemodialysis in the management of salt and water overload: a crossover trial at an academic hospital in Dakar, Senegal - Faye, Moustapha; Ba, Bacary; Keita, Niakhaleen; Ba, Sidy Mohamed; Coulibaly , Cheikh Ahmed Tidiane; Thioune, Ibrahima; Faye, Maria; Lemrabott, Ahmed Tall; Niang, Abdou; Ka, Elhadji Fary (African Journal of Nephrology, 2021)
Introduction: The aims of this study were to assess the impact of isonatraemic haemodialysis on reduction of interdialytic weight gain (IDWG) and blood pressure (BP) as well as its tolerability in our study population. Methods: This crossover trial, at the Aristide Le Dantec University Hospital in Senegal, was conducted on 32 patients with kidney failure who were stable on treatment with chronic haemodialysis. In the initial “control phase”, patients had nine haemodialysis sessions with a dialysate sodium (Na+) concentration (Na+ dialysate) of 138 mmol/L. The serum Na+ set point (SP) for each patient was calculated from three predialytic mid-week values. In the second phase, the “individualized phase”, patients had nine haemodialysis sessions with Na+ dialysate equal to their SP. Results: The mean age of the patients was 55.5 ± 12.1 years, with a male/female ratio of 1.3 and the most common cause of kidney disease was hypertension (47%). Mean predialytic serum Na+ concentration was 135.8 ± 1.9 mmol/L, with a mean intra-individual coefficient of variation of 2%. Mean interdialytic weight gain (IDWG) was 1.9 kg and 1.8 kg in the control and individualized phases, respectively (P = 0.75). A reduction in postdialytic systolic blood pressure (BP) was observed during the individualized phase (P = 0.04). A similar trend was noted in pre- and intradialytic BP but this was not statistically significant. Apart from headaches, which were more common in the individualized phase (P = 0.04), isonatraemic haemodialysis was well tolerated. Conclusions: IDWG as well as pre- and intradialytic BP were unaffected by isonatraemic haemodialysis. Postdialytic BP was significantly reduced. Introduction: Les objectifs de cette étude étaient d’évaluer l’impact de l’hémodialyse isonatrémique sur la réduction de la prise de poids inter-dialytique (PPID) et de la pression artérielle (PA) ainsi que sa tolérance dans notre population d’étude. Méthodes: Cet essai croisé a été mené au centre hospitalier universitaire Aristide Le Dantec de Dakar (Sénégal) chez des patients hémodialysés chroniques. Durant la première phase dite « phase contrôle », les patients ont eu neuf séances d’hémodialyse avec une concentration de sodium dans le dialysat (Na+ dialysat) de 138 mmol/L. Le set-point (SP) de la natrémie a été calculé pour chaque patient et correspondait à la moyenne de 3 natrémies pré-dialytiques en milieu de semaine. Durant la deuxième phase dite « phase individualisée », les patients ont eu neuf séances d’hémodialyse avec du Na+ dialysat égal à leur SP. Résultats: Trente-deux patients ont été inclus. L’âge moyen était de 55,5 ± 12,1 ans avec un ratio homme/femme de 1,3 et la néphropathie initiale la plus fréquente était l’hypertensive (47%). La natrémie pré-dialytique moyenne était de 135,8 ± 1,9 mmol/L, avec un coefficient de variation intra-individuel moyen de 2 %. La PPID moyenne était de 1,9 kg et 1,8 kg dans les phases de contrôle et individualisé, respectivement (P = 0,75). Une diminution de la PA systolique post-dialytique a été observée au cours de la phase individualisée (P = 0,04). Une tendance similaire sans significativité statistique a été notée sur les PA pré- et intra-dialytiques. Hormis les céphalées, plus fréquentes pendant la phase individualisée (P = 0,04), l’hémodialyse isonatrémique a été bien tolérée. Conclusions: La PPID, les PA pré- et intra-dialytiques n’ont pas été affectées par l’hémodialyse isonatrémique. La PA post-dialytique était significativement réduite.